Transcultural adaptation and psychometric properties of the Spanish version of Participation and Environment Measurement—Children and Youth (PEM-CY) - María Gómez-Vela; Mª Begoña Orgaz Baz; Isabel Vicario-Molina; Eva González Ortega; Marta Badia Corbella (BMC Psychology)
Abstract Background The Participation and Environment Measure for Children and Youth (PEM-CY) captures a child’s participation across home, school, and community-based activities as well as environmental factors perceived as supporting/hindering this participation. This tool has been translated into Spanish for use in the United States and Colombia but there are linguistic and sociocultural differences between these countries and Spain. Therefore, it is necessary to develop a country-specific measure to promote environment-based interventions for Spanish children with disabilities. This study aims to adapt the PEM-CY for use with children and youth in Spain, and to investigate its psychometric properties. Methods Seven hundred thirteen parents of children with (n = 233) and without (n = 480) disabilities, aged 5 to 17, completed the Spanish version of PEM-CY. For the test–retest reliability study, 30 of these parents completed the instrument twice. Results Internal consistency (0.58–0.97) and test–retest reliability (0.31–0.92) ranged from moderate to very satisfactory, according to Cronbach’s alpha and intraclass correlation coefficients. Discriminant validity, assessed through two-way ANOVA, was supported by significant differences between children with and without disabilities on participation and environment scales (p < .05). Some significant age differences were identified for participation at home and school. Validity was supported by a significant negative Pearson’s correlation (-0.32 to -0.41, p < .05) between desire for change and overall environmental supports. Conclusions The Spanish version of the PEM-CY is a valid and reliable tool to determine the participation and associated environmental factors in Spanish children and youth, with and without disabilities. It provides useful information for designing environment-based interventions to promote their participation.